2010
DOI: 10.1152/ajplung.00094.2010
|View full text |Cite
|
Sign up to set email alerts
|

A tandem repeat of a fragment of Listeria monocytogenes internalin B protein induces cell survival and proliferation

Abstract: -Hepatocyte growth factor (HGF) is critical for tissue homeostasis and repair in many organs including the lung, heart, kidney, liver, nervous system, and skin. HGF is a heterodimeric protein containing 20 disulfide bonds distributed among an amino-terminal hairpin, four kringle domains, and a serine protease-like domain. Due to its complex structure, recombinant production of HGF in prokaryotes requires denaturation and refolding, processes that are impractical for large-scale manufacture. Thus, pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Using functional HGF analogs is an alternative to HGF-based approaches in regenerative medicine. Recently, we demonstrated that the InlB321/15 protein, which is a HGFR ligand of bacterial origin, accelerates abrasion wound closure [16]. Results obtained in this work demonstrated that the InlB321/15 protein possesses hepatoprotective activity comparable with rhHGF taken in the same concentration.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Using functional HGF analogs is an alternative to HGF-based approaches in regenerative medicine. Recently, we demonstrated that the InlB321/15 protein, which is a HGFR ligand of bacterial origin, accelerates abrasion wound closure [16]. Results obtained in this work demonstrated that the InlB321/15 protein possesses hepatoprotective activity comparable with rhHGF taken in the same concentration.…”
Section: Discussionsupporting
confidence: 51%
“…Bacterial proteins have comparative advantages over recombinant human growth factors in regard to the accessibility, efficiency, and simplicity of production. Several studies have demonstrated the potential for InlB321 variants derived from different L. monocytogenes strains to stimulate the proliferation and motility of primary lung endothelial cells, keratinocytes, and Human Umblical Vein Endothelial Cells [13,14,15,16,17]. Recently, we showed that the variant InlB321 from L. monocytogenes strain VIMHA015 (InlB321/15) accelerated abrasion wound healing in mice [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in non-phagocytic cells, InlB is implicated in activating pro-survival signaling via the ERK1/2 kinases and STAT3 transcription factor. Although a precise transcriptional network of InlB signaling is yet to be determined, treating endothelial cells with recombinant InlB has been demonstrated to block the induction of apoptosis in response to angiotensin II, suggesting that these pathways could function to promote host cell survival during infection, thereby maintaining the intracellular niche of Lm [132]. In these instances, whether a transcriptional response is deliberately activated as a means of host manipulation can be difficult distinction to make, and is further complicated by the fact that blocking virulence factor activity often perturbs infection and pathogenesis (i.e., invasion or phagosome escape).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of InlB to Met mimics HGF signaling and induces membrane ruffling and cell scattering via the activation of the PI3-K, which is a process critical for internalization of L. monocytogenes [99]. [103]. They demonstrated that this tandem dimmer induces signaling through ERK1/2, PI3-K/Akt, and STAT3 pathways, and has improved migratory activity.…”
Section: Listeria Infection and Met Signalingmentioning
confidence: 99%